PEMANFAATAN INTERNET OF THINGS (IOT) PADA PERANCANGAN SISTEM BANGUNAN CERDAS - Komang Bagus Dwi Widiatama Putra; I Nyoman Satya Kumara; I Wayan Sukerayasa; I Made Arsa Suyadnya (Jurnal SPEKTRUM, 2025)
The development of Internet of Things (IoT) technology has made a significant contribution to the design of smart building systems. This research discusses the utilization of IoT in designing smart building systems based on previous studies. The focus of the discussion includes the use of controllers, various types of sensors and control devices, and system scope. By understanding the use of IoT devices and the approaches used in prior research, this study is expected to serve as a reference in the development of smart building systems to be more adaptive and efficient in the future.